Perlindungan Hukum Bagi Masyarakat Hukum Adat Yang Lingkungan Hidupnya Tercemar - Natalia Lidya Pohwain; Jemmy Jefry Pietersz; Revency Vania Rugebregt (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The legal issues in this paper include (1) Is there legal protection for indigenous peoples who are victims of pollution and (2) How are legal remedies related to legal protection for indigenous peoples whose environment is polluted.Purposes of the Research: The results of the discussion of the authors of this thesis are obtained that in the legislation providing legal protection arrangements for indigenous peoples and for indigenous peoples as victims of pollution, can use administrative sanctions as a form Law enforcement in the form of written warnings, government coercion, freezing of environmental permits, to revocation of environmental permits.Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: The results of the discussion of the authors of this thesis are obtained that in the legislation providing legal protection arrangements for indigenous peoples and for indigenous peoples as victims of pollution, can use administrative sanctions as a form Law enforcement in the form of written warnings, government coercion, freezing of environmental permits, to revocation of environmental permits.